Investigation of blood pressure regulation schemes - Chai, Chang Yong (2009)
For many years, hypertension is a critical concern in the postoperative care for patient. It is very crucial that hypertension is being treated at the early stage to prevent it from further complication. Sodium Nitroprusside (SNP) is one of the commonly used antihypertension agents for treatment during the postoperative care. Nevertheless, when not carefully handed, the side effect of SNP might cause harm to the patient’s health. Hence, continuous monitoring and careful control of the infusion of drug is required. Since the middle 1970s, many researches have been conducted using various types of feedback control system to regulate blood pressure through the infusion of antihypertension drug [5]. Till date, there are a number of different types of blood pressure control systems designed and developed used for different blood pressure [5]. Most of the previous studies have shown that the focus of the study is on developing the control system and there is lack of focus on the development of the patient model. In this project, the study of blood pressure regulation schemes and patient models is being conducted. Simulations are being conducted on the selected patient model to verify the usability of the patient model for future use and development of new control system. The hardware provided for the study is also being interfaced and evaluated in the process.